2022
DOI: 10.1093/rap/rkac039
|View full text |Cite
|
Sign up to set email alerts
|

Experience with telemedicine amongst rheumatology clinicians during the COVID-19 pandemic: an international survey

Abstract: Objective To assess rheumatology clinicians’ perceptions of telemedicine as well as their experiences before and during the COVID-19 pandemic. Methods We conducted a cross-sectional online survey and collected responses from rheumatology clinicians worldwide between November 2020 and February 2021, regarding use and perceptions of telemedicine in rheumatology. We summarized data with descriptive statistics and qualitative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Despite some digital patient management platforms have been in place already before 2020, they were telephone consultations, and emerging video consultations have kept patient care at a low level. 3 …”
Section: Covid-19 Lockdown: the Ultimate Stress Test For Remote Patie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some digital patient management platforms have been in place already before 2020, they were telephone consultations, and emerging video consultations have kept patient care at a low level. 3 …”
Section: Covid-19 Lockdown: the Ultimate Stress Test For Remote Patie...mentioning
confidence: 99%
“…The COVID-19 lockdown was a sudden and unexpected stress test for remote patient care in practices and hospitals. Despite some digital patient management platforms have been in place already before 2020, they were telephone consultations, and emerging video consultations have kept patient care at a low level 3…”
Section: Covid-19 Lockdown: the Ultimate Stress Test For Remote Patie...mentioning
confidence: 99%
“…Furthermore, patients have reported that self-monitoring of the disease enables them to see the connection between behavioral factors (eg, taking medications and lifestyle choices) and disease concerns [ 1 ]. However, a survey regarding the use of digital technology during the COVID-19 pandemic revealed that HPs considered remote care inferior to face-to-face visits [ 21 ]. In a recent study, both patients and HPs considered remote care inferior to face-to-face visits, but remote care was convenient for patients in relation to reduced traveling and waiting times [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remote care is in an early phase, and research on facilitators and barriers is required in order to integrate and adopt remote care into standard practice [ 11 14 ]. Earlier studies on facilitators and barriers to remote care in rheumatology have primarily focused on experiences from rheumatologists during the COVID-19 pandemic [ 10 , 15 , 16 ]. Since these, previous studies were conducted during the COVID-19 pandemic when physical consultations were limited to a minimum, there may be a bias towards more positive attitudes concerning remote care.…”
Section: Introductionmentioning
confidence: 99%